Scale and the wartime Saturday Evening Post: A geographical strategy of nation building - Louise Appleton (Unité Mixte de Recherche 8504 Géographie-cités, 2002)
Over the last ten years, geographical scale has been at the forefront of academic enquiry in political geography. Scale has been used to demonstrate the social construction of space, and to illustrate how space is framed in particular ways to satisfy political ends. What scale literature lacks, however, is an acknowledgement of how socio-cultural actors play an important role in these constructions and how cultural (as well as political and economic) processes are thoroughly implicated in the construction of space. This paper demonstrates, through an empirical study of national identity in the Saturday Evening Post during World War Two, how the national space is articulated through different geographical scales. It shows how scales frame particular images of the nation so that readers are provided with an understanding of the meaning of the United States of America, and their place in it. The paper concludes that this application of scale to cultural geographical enquiries is useful for demonstrating the political significance of geographical scale in ordering civil society.